Navigating Human Resource Challenges and Key Success Factors in the Transition to Integrated Logistics Systems: A Change Management Perspective - dyah palupiningtyas; Krisnawati Setyaningrum Nugraheni; Ray Octafian (Politeknik APP Jakarta, 2024)
This study examines the process of change management, identifies human resource obstacles, and explores critical success factors in deploying an integrated logistics system at PT Kubota Indonesia. Employing a qualitative approach and case study methodology, data were gathered via semi-structured interviews, observations, and document analysis. Findings reveal that PT Kubota Indonesia employs a systematic change management strategy that considers human and cultural dimensions. Despite encountering challenges like deficiencies in technical expertise and resistance to change, the company effectively addressed these issues through proactive communication, staff engagement, training initiatives, and strong management backing. Key drivers of success identified encompass executive support, transparent communication, employee involvement, comprehensive training, and adept cultural change management. This study contributes insights into a comprehensive approach to change management, emphasizing the synchronization of technical aspects with human and cultural factors to ensure the triumphant integration of an advanced logistics system.